A novel Apaf-1–independent putative caspase-2 activation complex - Read, Stuart H. (The Rockefeller University Press, 2002)
CVaspase activation is a key event in apoptosis execution. In stress-induced apoptosis, the mitochondrial pathway of caspase activation is believed to be of central importance. In this pathway, cytochrome c released from mitochondria facilitates the formation of an Apaf-1 apoptosome that recruits and activates caspase-9. Recent data indicate that in some cells caspase-9 may not be the initiator caspase in stress-mediated apoptosis because caspase-2 is required upstream of mitochondria for the release of cytochrome c and other apoptogenic factors. To determine how caspase-2 is activated, we have studied the formation of a complex that mediates caspase-2 activation. Using gel filtration analysis of cell lysates, we show that caspase-2 is spontaneously recruited to a large protein complex independent of cytochrome c and Apaf-1 and that recruitment of caspase-2 to this complex is sufficient to mediate its activation. Using substrate-binding assays, we also provide the first evidence that caspase-2 activation may occur without processing of the precursor molecule. Our data are consistent with a model where caspase-2 activation occurs by oligomerization, independent of the Apaf-1 apoptosome.